Therapeutic effects of Lactobacillus rhamnosus, thymol and their combination against neurotoxicity in propionic acid (PA)-induced autistic rats: insights into the role of the Nrf2/HO-1, Wnt3/β-catenin/GSK3β BDNF/p-TrkB/CREB, pI3K/Akt/mTOR, AMPK/SIRT-1, and PERK/CHOP/Bcl-2 pathways - Salem, Hoda A.; Rizk, Nermin I.; AbdelSalam, Moustafa H.; Ahmed, Rehab; Atteia, Hebatallah Husseini; Hamdan, Ahmed M. E.; Alghamdi, Areej A.; Alghusn, Manar A.; Alatawi, Renad A.; Atallah, Rawan A.; Alfuhaymani, Maryam M.; Alqahtani, Hatun A.; et al. (Frontiers in Pharmacology, 2026)
BackgroundAutism spectrum disorder (ASD) is a neurodevelopmental disease characterized by repetitive behaviors and a lack of social communication. The role of probiotics, phytochemicals and their combination phytochemicals as treatment options for ASD is still under study.ObjectiveThis study aimed to evaluate the associated molecular pathways and explore the impact of Lactobacillus rhamnosus (L. rhamnosus), thymol (Thy) and their combination on propionic acid (PA)-induced ASD rats.MethodsFifty 3-week-old male albino rat pups were randomly distributed into five groups. The groups included a control group, a PA-induced ASD group, in which PA (250 mg/kg, p.o.) was administered for 3 days, and three other groups that received PA (250 mg/kg, p.o.) for 3 days along with either L. rhamnosus (1 × 10^6 CFU/day, p.o), Thy (30 mg/kg/day, p.o), or both. Brain tissues were collected for biochemical, histological, and immunohistochemical studies following behavioral evaluations.ResultsCompared with the group administered only PA, treatment with L. rhamnosus, Thy and their combination significantly improved the neurobehavioral deficits in the autistic group. Improvements were observed in tests assessing memory consolidation, learning capacity, attention, spatial memory, locomotor activity, and contextual information processing. In addition to histopathological improvements, L. rhamnosus, Thy and their combination demonstrated notable ameliorative effects on PA-induced abnormalities in brain neurotransmitters, oxidative stress, inflammation, apoptosis, and endoplasmic reticulum (ER) stress and autophagy biomarkers. Furthermore, treatment with L. rhamnosus, Thy and their combination improved abnormalities in the tested biomarkers and modulated associated pathways, including significant upregulation of BDNF, TrkB, CREB, Nrf2, and HO-1 content and downregulation of TLR4/NF-κB-mediated neuroinflammation, leading to substantial improvements in ASD symptoms.ConclusionOur results suggest that L. rhamnosus, Thy and their combination have promising therapeutic potentials in alleviating biochemical and behavioral deficits in PA-induced autism. These effects may be mediated by halting apoptosis, inflammation, and endoplasmic reticulum stress, inducing autophagy, and improving different biomarkers and modulation pathways, such as Wnt3/β-catenin/GSK3β, pI3K/p-Akt/mTOR, and BDNF/p-TrkB/CREB.